Flight vehicle system identification : a time-domain methodology - Jategaonkar, Ravindra V. (Progress in astronautics and aeronautics ;, 2015)
This book offers a systematic approach to flight vehicle system identification and covers the time-domain methodology. It addresses theoretical and practical aspects of parameter estimation methods, including those in the stochastic framework focusing on nonlinear models, cost function, optimization methods, and residual analysis. A pragmatic and balanced account of pros and cons in each case is provided. It presents data gathering and model validation, covering large-scale and high-fidelity modeling. Real-world problems dealing with a variety of flight vehicle applications are addressed, and solutions are provided. Examples include: estimation of aerodynamic stability and control derivatives from flight data; flight-path reconstruction; nonlinearities in control surface effectiveness; stall hysteresis; unstable aircraft; flexible aircraft model integrating rigid-body and structural dynamics; wake vortex encounters; and other critical considerations. --